2018
DOI: 10.1016/j.jenvrad.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of tritiated water, zinc and dissolved organic carbon: Assessing interactive bioaccumulation and genotoxic effects in marine mussels, Mytilus galloprovincialis

Abstract: Release of tritium (H) in the marine environment is of concern with respect to its potential bioaccumulation and detrimental impact on the biota. Previous studies have investigated the uptake and toxicity of this radionuclide in marine mussels, and the interaction of H with dissolved organic ligands and elevated temperature. However, despite the well-established view that toxicity is partly governed by chemical speciation, and that toxic effects of mixture of contaminants are not always additive, there have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
(81 reference statements)
2
16
0
Order By: Relevance
“…This technique, which used polymerase chain reaction (PCR) primers to amplify a specific region of the Glu-5' gene (Gene Bank accession no. D63778), confirmed the species used in our laboratory to be M. galloprovincialis (Pearson et al, 2018). We further confirmed the species prior to the present set of experiments using the same methodology (data not included).…”
Section: Mussel Exposure Conditionssupporting
confidence: 78%
See 4 more Smart Citations
“…This technique, which used polymerase chain reaction (PCR) primers to amplify a specific region of the Glu-5' gene (Gene Bank accession no. D63778), confirmed the species used in our laboratory to be M. galloprovincialis (Pearson et al, 2018). We further confirmed the species prior to the present set of experiments using the same methodology (data not included).…”
Section: Mussel Exposure Conditionssupporting
confidence: 78%
“…Adult MG and DP were collected from Trebarwith strand (Dallas et al, 2013) and Bude, Cornwall, UK (50.828059, -4.549053), respectively. Maintenance of the mussels has been described in detail in previous publications (Dallas et al 2013;Dallas et al 2016a;Pearson et al 2018). As Hilbish et al (2002) reported the occurrence and distribution of Mytilus edulis, M. galloproviancialis and their hybrids in the coastal regions of south-west England, we ensured species homogeneity in our experiments based on the method of Inoue et al (1995).…”
Section: Mussel Exposure Conditionsmentioning
confidence: 88%
See 3 more Smart Citations